Microbial community in a sediment-hosted CO2 lake of the southern Okinawa Trough hydrothermal system - Inagaki, F.; Kuypers, M.; Tsunogai, U.; Ishibashi, J.; Nakamura, K.; Treude, T.; Ohkubo, S.; Nakaseama, M.; Gena, Kaul; Chiba, H.; Hirayama, H.; Nunoura, T.; et al. (National Academy of Sciences, 2006)
Increasing levels of CO2 in the atmosphere are expected to cause climatic change with negative effects on the earth’s ecosystems and human society. Consequently, a variety of CO2 disposal options are discussed, including injection into the deep ocean. Because the dissolution of CO2 in seawater will decrease ambient pH considerably, negative consequences for deep-water ecosystems have been predicted. Hence, ecosystems associated with natural CO2 reservoirs in the deep sea, and the dynamics of gaseous, liquid, and solid CO2 in such environments, are of great interest to science and society. We report here a biogeochemical and microbiological characterization of a microbial community inhabiting deep-sea sediments overlying a natural CO2 lake at the Yonaguni Knoll IV hydrothermal field, southern Okinawa Trough. We found high abundances (>109 cm3) of microbial cells in sediment pavements above the CO2 lake, decreasing to strikingly low cell numbers (107 cm3) at the liquid CO2CO2-hydrate interface. The key groups in these sediments were as follows: (i) the anaerobic methanotrophic archaea ANME-2c and the Eel-2 group of Deltaproteobacteria and (ii) sulfur-metabolizing chemolithotrophs within the Gamma- and Epsilonproteobacteria. The detection of functional genes related to one-carbon assimilation and the presence of highly 13C-depleted archaeal and bacterial lipid biomarkers suggest that microorganisms assimilating CO2 andor CH4 dominate the liquid CO2 and CO2-hydrate-bearing sediments. Clearly, the Yonaguni Knoll is an exceptional natural laboratory for the study of consequences of CO2 disposal as well as of natural CO2 reservoirs as potential microbial habitats on early Earth and other celestial bodies.